Line Outage Vulnerabilities of Power Systems : Models and Indicators - Ha Dinh Truc
Chapter I. Access to electricity is a vulnerable right; Chapter II. Contingency analysis of AC power systems 15; Chapter III. Topological indicators for mapping vulnerability of power systems; ...